ML-BASED SPECIFIC SCARCITY MITIGATION AND INTELLIGENT FARMING IN RURAL AREAS (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is one of the most important sectors for ensuring not only food security but also nutrition security, as well as sustainable development and the reduction of poverty. Fertility of the soil, ensuring that the soil retains an adequate level of fertility, and, most importantly, ensuring that farmers receive favorable benefits at the appropriate time. With the advancement of technology and as conditions improve in agriculture due to technical monitoring and testing of crops, precision farming technology can potentially improve fertility in ways such as increased disease awareness. Achieving harmony in agricultural production is the most fundamental and essential form of work, and it is an essential component in human beings and many other industries. Its only requirement is food. The farming techniques discovered over the years have gradually been improved to make them more profitable, increase crop yields, and reduce the amount of irrigation wasted. Because of this, they will become more aware of the benefits of utilizing modern technology to assist farmers. Utilizing is where developments like data analysis, nanotechnology, and machine learning come from.